Characterization of lymphocyte subsets as a tool of assessment of histological disease activity pattern in ulcerative colitis - Ghazi, Hayder F. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: In Ulcerative colitis (UC), the presence of a persistently elevated number of T cells in the inflamed area with respect to the activity of the disease suggesting bad prognosis. This study was done to evaluate cellular immune response in different disease activity patterns and its possible implication in evaluation of disease activity.Materials and methods: This study included Forty seven archived paraffin-embedded samples of ulcerative colitis; these samples diagnosed and graded for disease activity. Then dualimmunofluorescence staining was used for phenotyping of lymphocytic infiltrate (CD3- CD19) and (CD4-CD8). A total and differential T cell as well as plasma cell count was recorded in these UC tissue samples. Non parametric Kruskal-Wallis test was used to compare the median cell counts among different study groups.Results: There is higher lymphocytic infiltrate for all types of cells when UC samples compared with control samples with highly statistical significant difference, T cells represents the major constituents of colonic mucosal infiltrate (86.89%) and about 75.79% were CD4 positive T cells. T-cell subsets and plasma cell have high statistical significant difference (p≤0.001) according to histological grade. Furthermore, with the histological grade the highest association found with T lymphocytes (r=0.944) followed by T helper (r=0.821), T cytotoxic (r=0.653) and B lymphocyte (r=0.237).Conclusions: Qualitative and semi quantitative characterization of lymphocytes subsets was useful in the assessment of different histological grades of UC disease activity.